Colonial encounters: essays in early American history and culture ; [from May 21 to 24, 2002, the German Association for American Studies held its 49th Annual Meeting in Lutherstadt Wittenberg] - Grabbe, Hans-Jürgen (American studies, 2003)
The German Association for American Studies held its 49th annual conference in Wittenberg as a contribution to the quincentenary of Martin Luther University Halle-Wittenberg. The theme, "Colonial Encounters," suited the occasion, since Halle had maintained close religious, intellectual, and commercial relations with British North America. Twenty-three original contributions to the conference appear in this volume. The implications of the conference title are explored, for example, with regard to Early American Studies, projects for environmental manipulation, and the Spanish frontier. Other essays focus on theories of civilization, Native American identity, and representations of encounters in music, visual arts, and material culture. Still others discuss displacement and transculturation. Both colonial America and the early national period of the American republic are within the book's scope
Keywords: United States -- Congresses -- History -- Colonial period, ca. 1600-1775; United States -- Congresses -- Civilization -- To 1783; United States -- Congresses -- Ethnic relations; Europe -- Congresses -- Colonies -- America; Konferenzschrift -- 2002 -- Wittenberg; Geschichte 1700-1815; Kolonialismus; Künste; Geschichte 1600-1789; Kolonie; USA